ANALISIS ABILITY TO PAY DAN WILLINGNESS TO PAY PENGGUNA JASA KERETA API BANDARA KUALANAMU (AIRPORT RAILINK SERVICE) - Julien Julien; Kasyful Mahalli (Departemen Ekonomi Pembangunan USU, 2014)
The objectives of this research are to analyze the users’ ability and willingness to pay the Kuala Namu airport railink services, to find the ideal fare of the train services and to investigate the basic consideration in determining the services fare from PT.Railink. Data is collected by interviews based on the questionnaire. Moreover, in analyzing the data, household budget method and stated preference method are used to measure the ability and the willingness respectively. The results shows that the average respondent’s ability to pay is Rp 78,375 and the average respondent’s willingness to pay is Rp 60,375. However, after the increase in quality of priority, the average respondent’s ability to pay will become Rp 71,375 with the average amount of money that is willing to be added by respondent is Rp 22,632. In determining the fare, PT. Railink has considered the operation fee and the quality of services given to the customers as its primary reasons. Based on the current fare, respondent who have the ability to pay is only 50%. The research reveal that the ideal fare for the train services is Rp 69.375, which will increase the percentage of respondents who have the ability to pay to 72.5%Key Words : Ability to Pay (ATP), Willingness to Pay (WTP), Ideal Fare, PT.Railink.